The ALMA early science view of FUor/EXor objects – V. Continuum disc masses and sizes. Issue 4 (27th November 2017) - Cieza, Lucas A; Ruíz-Rodríguez, Dary; Perez, Sebastian; Casassus, Simon; Williams, Jonathan P; Zurlo, Alice; Principe, David A; Hales, Antonio; Prieto, Jose L; Tobin, John J; Zhu, Zhaohuan; Marino, Sebastian
Abstract: Low-mass stars build a significant fraction of their total mass during short outbursts of enhanced accretion known as FUor and EXor outbursts. FUor objects are characterized by a sudden brightening of ∼5 mag at visible wavelengths within 1 yr and remain bright for decades. EXor objects have lower amplitude outbursts on shorter time-scales. Here we discuss a 1.3 mm Atacama Large Millimeter/submillimeter Array (ALMA) mini-survey of eight outbursting sources (three FUors, four EXors, and the borderline object V1647 Ori) in the Orion Molecular Cloud. While previous papers in this series discuss the remarkable molecular outflows observed in the three FUor objects and V1647 Ori, here we focus on the continuum data and the differences and similarities between the FUor and EXor populations. We find that FUor discs are significantly more massive (∼80–600 M Jup ) than the EXor objects (∼0.5–40 M Jup ). We also report that the EXor sources lack the prominent outflows seen in the FUor population. Even though our sample is small, the large differences in disc masses and outflow activity suggest that the two types of objects represent different evolutionary stages. The FUor sources seem to be rather compact ( R c  < 20–40 au) and to have a smaller characteristic radius for a given disc mass when compared to T Tauri stars. V1118 Ori, the only known close binary system in our sample, is shown to host a disc around each one of the stellar components. The disc around HBC 494 is asymmetric, hinting at a structure in the outer disc or the presence of a second disc.